Simulation of the effect of shading on monocrystalline solar module technology under hot spot condition - Anjos, R.S. (2017)
This paper focuses on the monocrystalline PV module technology subjected to operation conditions with some cells partially or fully shaded. A shaded cell under hot-spot condition operating at reverse bias are dissipating power instead of delivering power. A thermal model allows analyzing the temperature increase of the shaded cells of the module under hot-spot condition with or without protection by a bypass diode. A comparison of the simulation results for a monocrystalline PV module without shading and with partial or full shading is presented.